Q: K plus 6K-13 equals 57

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

k = 0.1

It simplifies to 7k = 49 which gives k = 7.

If: k+3=-3 Then: k=-3-3 k=-6

j=-3 and k=2

They are +/- 5*sqrt(2)

Related questions

Yes, they are exactly the same, both of them increment k in 1.

k equals 5.6

123

k = 0.1

50

It simplifies to 7k = 49 which gives k = 7.

If: k+3=-3 Then: k=-3-3 k=-6

k=4

R = 65*e-5k = 65/(0.006738)k

neg(-k) + neg(-k) = k + k = 2k = 4

k = -1

j=-3 and k=2